2013
DOI: 10.1371/journal.pone.0083520
|View full text |Cite
|
Sign up to set email alerts
|

Plant Virus Differentially Alters the Plant's Defense Response to Its Closely Related Vectors

Abstract: BackgroundThe whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae), is one of the most widely distributed agricultural pests. In recent years, B. tabaci Q has invaded China, and Q has displaced B in many areas now. In a number of regions of the world, invasion by B and/or Q has been followed by outbreaks of tomato yellow leaf curl virus (TYLCV). Our previous study showed TYLCV directly and indirectly modified the feeding behavior of B. tabaci in favor of Q rather than B.Methodology/Principal FindingsIn this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 62 publications
3
48
0
1
Order By: Relevance
“…A previous study demonstrated that exogenous SA application led to increased SA levels in tomato plants (Shi et al . ). Increased titres of SA ingested by whiteflies, or changes in phloem resulting from increased SA, potentially affect within‐host symbiont titres.…”
Section: Methodsmentioning
confidence: 97%
“…A previous study demonstrated that exogenous SA application led to increased SA levels in tomato plants (Shi et al . ). Increased titres of SA ingested by whiteflies, or changes in phloem resulting from increased SA, potentially affect within‐host symbiont titres.…”
Section: Methodsmentioning
confidence: 97%
“…Our latest study showed that SA content was always higher in leaves infested with viruliferous B than with viruliferous Q5. Furthermore, the relative gene expression associated with SA signaling was increased by the feeding of viruliferous B but not by the feeding of viruliferous Q5. Zhang et al (2012)27 demonstrated that co-infection of the begomovirus tomato yellow leaf curl China virus (TYLCCNV) and its betasatellite can repress JA-regulated defenses of tobacco against invasive whiteflies and accelerate population increases of the insects.…”
mentioning
confidence: 85%
“…Indeed, differing persistence times might be a major explanation for the observation that manipulation effects are more frequently reported for intermediate than for final hosts, at least as long as all hosts are animals (Holmes and Bethel, 1972). Plant pathogens, by contrast, require mobile vectors for their dispersal among their immobile final hosts and, therefore, frequently manipulate the quality of their host plant for the vectors (Belliure et al, 2010;Mauck et al, 2010Mauck et al, , 2014aLuan et al, 2013;Shi et al, 2013) as well as the feeding decisions that are taken by their vectors (Stafford et al, 2011;Ingwell et al, 2012;Mann et al, 2012;Fang et al, 2013;Rajabaskar et al, 2014). These changes can be very fine-tuned: for example, plant viruses with a persistent mode of transmission require vectors to feed for a prolonged period of time on infected hosts and, thus, usually tend to improve the quality of the host plants for the vectors.…”
Section: Why Don't All Parasites Manipulate?mentioning
confidence: 99%